The effects of phenoxodiol on the cell cycle of prostate cancer cell lines - Mahoney, S.; Arfuso, Frank; Millward, M.; Dharmarajan, A. (BioMed Central Ltd, 2014)
Background: Prostate cancer is associated with a poor survival rate. The ability of cancer cells to evade apoptosis and exhibit limitless replication potential allows for progression of cancer from a benign to a metastatic phenotype. The aim of this study was to investigate in vitro the effect of the isoflavone phenoxodiol on the expression of cell cycle genes. Methods: Three prostate cancer cell lines-LNCaP, DU145, and PC3 were cultured in vitro, and then treated with phenoxodiol (10 μM and 30 μM) for 24 and 48 h. The expression of cell cycle genes p21WAF1, c-Myc, Cyclin-D1, and Ki-67 was investigated by Real Time PCR. Results: Here we report that phenoxodiol induces cell cycle arrest in the G1/S phase of the cell cycle, with the resultant arrest due to the upregulation of p21WAF1 in all the cell lines in response to treatment, indicating that activation of p21WAF1 and subsequent cell arrest was occurring via a p53 independent manner, with induction of cytotoxicity independent of caspase activation. We found that c-Myc and Cyclin-D1 expression was not consistently altered across all cell lines but Ki-67 signalling expression was decreased in line with the cell cycle arrest. Conclusions: Phenoxodiol demonstrates an ability in prostate cancer cells to induce significant cytotoxicity in cells by interacting with p21WAF1 and inducing cell cycle arrest irrespective of p53 status or caspase pathway interactions. These data indicate that phenoxodiol would be effective as a potential future treatment modality for both hormone sensitive and hormone refractory prostate cancer.